Relationship between job stress and organisational commitment among public servants in Pontian, Johor - Ahmad, Sa'odah; Roslan, Nor Fameza (Zes Rokman Resources, 2016)
This study was conducted to determine the relationship between job stress and organisational commitment among public servant in Pontian, Johor. 262 public servants were chosen as respondents of this study through random sampling technique. Job Stress Scale (Crank, Regoli, Hewiit & Carlberson, 1995) and Organisational Commitment Scale (Meyer and Allen, 1997) were used to measure job stress and organisational commitment respectively. Result revealed that there were significant negative relationships between job stress and organisational commitment (affective r=-.272, p=.000), continuance (r=-.160, p=.01), normative (r= -.231, p=.000). The findings gave an implication that worker with low job stress will have a high organisational commitment. Therefore, employer and organisation should strive to take appropriate steps in reducing job stress and providing adequate and good facilities at work place, thus ensuring that worker has a high level of organisational commitment. High organisational commitment will contribute to worker’s high productivity that will not only benefit the worker himself but also the employer and organisation.